Silo-Guard for forage sorghum silage - K. Bolsen; H. Ilg (Kansas Agricultural Experiment Station Research Reports, 1980)
Two forage sorghum silages (29 to 30% DM) were made October 1 to 3, 1978; one ensiled without additive (control), the other with 1.5 lbs. of Silo-Guard added per ton of fresh crop. Silos were opened after 36 days, and each was full-fed to 15 yearling steers (3 pens of 5 steers) during a 90-day trial (November 9, 1978, to February 7, 1979). Rations contained 84% silage and 16% soybean meal supplement on a DM basis.
Keywords: Cattlemen& #x27; s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Silo-Guard; Sorghum silage